THE JAT PANCHAYAT IN THE KAIKADI COMMUNITY: A STUDY OF LAXMAN MANE'S AUTOBIOGRAPHY ‘AN OUTSIDER’ - Kadam, Kalyan R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores Dalit literature through Laxman Mane's autobiography "An Outsider." It highlights the life of the Kaikadi nomadic tribe and the role of their Jat Panchayat system. The Panchayat enforces strict rules, often leading to social exploitation like excommunication. Using simple examples from the book, the paper shows how these traditions clash with modern ideas. It argues that Dalit writings challenge caste oppression and call for social justice.